Firm inattention and the efficacy of monetary policy: A text-based approach - Wenting Song; Samuel Stern (Bank of Canada, 2022)
This paper provides direct evidence of the importance of firm attention to macro-economic dynamics. We construct a text-based measure of firm attention to macro-economic news and document firm attention that is polarized and countercyclical. Differences in attention lead to asymmetric responses to monetary policy: expansionary monetary shocks raise market values of attentive firms more than those of inattentive firms, and contractionary shocks lower values of attentive firms by less. We use the measure to calibrate a quantitative model of rationally inattentive firms with heterogeneous costs of information. Less attentive firms adjust prices slowly in response to monetary innovations, which yields non-neutrality. As average attention varies over the business cycle, so does the efficacy of monetary policy.
Keywords: D83; E44; E52; 330; Business fluctuations and cycles; Inflation and prices; Monetary policy